Intrinsic and Extrinsic Motivation in English Language Learning: A Qualitative Case Study of English Literature Students at Universitas Kristen Cipta Wacana - Yasin, Mohammad Ilham; Jauhari, Iman Jauhari; Dwiananto, Gigih; Wibowo, Akbar (Universitas Kristen Cipta Wacana, 2025)
The intrinsic and extrinsic motivational variables that affect students' English language acquisition in the English Literature program at Universitas Kristen Cipta Wacana are examined in this study. The study employs a qualitative case study technique to analyze individual, academic, and social variables that influence students' participation in English education. Semi-structured interviews and focus group conversations with 10 carefully chosen subjects were used to gather data. Thematic analysis showed that students' intrinsic motivation is frequently derived from their love of literature, personal pleasure in learning English, and aspiration for self-improvement. In the meanwhile, external incentives are influenced by academic demands, parental expectations, and professional ambitions. The research sheds light on the two roles of motivation in language acquisition and makes pedagogical recommendations for encouraging long-term learner involvement.